Energy consumption considerations in dynamic wireless sensor networks with nodes and base stations mobility - Al-Rousan, Mohammad (2010)
Energy conservation is a critical issue in the design of sensor networks since the sensor nodes are battery-powered. This paper proposes a wireless sensor network with mobile sensor nodes and base stations to prolong the network lifetime. The movement of base stations inside the covered region is done according to the evolution of current events. The proposed scheme is based on minimising the average consumed energy for every active sensor when data is transmitted. Performance evaluation of the proposed wireless dynamic sensor network is done with a comparison of the network lifetime with the case of static sensor nodes and the base stations.